Projeto experimental de Publicidade e Propaganda : Associação Beneficente Lar da Criança - Martins Júnior, Amauri Imbraim (2019)
Transforming life's obstacles into opportunities to write a happy new chapter is part of the important service that the Lar da Criança in Erechim provides to its community. Active since 1980, the main objective of the organization is to receive children and adolescents at risk and socially vulnerable, upon request for revocation of the Guardianship Council and Court of Childhood and Adolescence. More than that, the hosts are offered a cheerful and outgoing atmosphere, full of love and love, until the moment when your family is able to welcome you back. The purpose of this project is to create a communication plan for the Lar da Criança, clarify its operation and increase the collection of materials for the institution's support. For these two campaigns were planned, one aimed at collecting and attracting partner companies from the Home and another institutional campaign, in order to show the most joyful and important form of the ONG.